Editor’s Preface to Essay Section on Methods and Analysis in Fringe Science - Houran, James (Journal of Scientific Exploration, 2023)
The following content constitutes an informal but fortuitous collection that speaks to methods and analysis in fringe science. Articles about model-building or theory formation on anomalous phenomena often garner the strongest interest for understandable reasons, but the underlying approaches and techniques that drive charge- or challenge- type discoveries arguably represent some of most fascinating and important information. To be sure, descriptions of flexible or innovative methods can inspire and support work across many different academic disciplines [for a discussion, see: Houran, J. (2022). An introduction and mission of building bridges to reach the unknown. Journal of Scientific Exploration, 36, 3-7. https://doi.org/10.31275/20222439]. Thus, the JSE welcomes submissions that present newly developed (or specifically tailored) methods and instrumentation for studies in anomalistics. We further encourage readers to explore the many peer-reviewed journals devoted to analytics, instrumentation, and research design. Interested readers can search and learn about such journals at aggregator sites like Publons.com or Resurchify.com, but Table 1 below presents a convenient selection of 25 examples that arguably are worthy of attention with good-to-high impact factors.